URGENSI KELUARGA DALAM MENDIDIK ANAK - Nurfuadi Nurfuadi (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
family is fist and eminent institution for growing and developing children. If family’s atmosphere is fine and enjoyable,children will grow perfectly. Otherwise, children development will be hampered. Mother’s role is critical, because she’s thatmanage and makehouse comfortable for all dweller, and become equal partner for her husband, that loving each other. Pious wife (solikhah) has wisdom toeducate her children well to become pious people, know their right and obligation, that defined by religion